Anatomy of Failure: Japan-U.S.S.R. Negotiations on Siberian Oil Development - Braden, Wythe E. (Tufts Archival Research Center, 2005)
Volume 5, Issue 1. Winter The failure of the Japanese-U.S.S.R. Siberian Oil negotiations has yet to reach its fatal nadir as the irony of Japanese-Soviet geographical proximity has not been universally realized. Wythe Braden attempts to bring the reader closer to this paradox through his study of the Japanese press, government and business community during the course of the negotiations. His conclusions show that the objective elements of the negotiations themselves were so tragically flawed that the outcome could not be anything but fruitless.